QuEChERS extraction for multi-residue analysis of PCBs, PAHs, PBDEs and PCDD/Fs in biological samples. - Cloutier, Pierre-Luc; Fortin, Frédérik; Groleau, Paule Emilie; Brousseau, Pauline; Fournier, Michel; Desrosiers, Mélanie (Talanta, 2017)
International audience In this study, a fast and rugged method is presented for the analysis of PCBs, PAHs, PBDEs and PCDD/Fs in biological tissues using a simple Quick, Easy, Cheap, Efficient, Rugged and Safe (QuEChERS) extraction and a clean-up by Gel Permeation Chromatography (GPC) and silica Solid Phase Extraction (SPE). Development was performed on blue mussels (Mytilus edulis) and Atlantic salmon (Salmo salar) for evaluation of two ranges of lipid and water content of biological tissues. Statistical validation was performed with Atlantic salmon samples. Forty-five PAHs were analyzed including the priority list of the US EPA and the European Union with 41 PCBs, 24 PBDEs and 17 PCDD/Fs. Instrumental analyses were performed on Gas Chromatography - High Resolution Mass Spectrometry (GC-HRMS). Accuracy was evaluated for PCBs and PCDD/Fs with a certified reference material furnished by the National Research Council Canada (NRCC) and also compared with results obtained by the conventional Soxhlet extraction. Statistical validation showed recoveries for PCBs, PAHs, PBDEs and PCDD/Fs close to 100% with average Relative Standard Deviation (RSD) lower than 10% and internal standard recoveries in the range of 70% with average RSD ranging from 5-15%. Average calculated Method Detection Limits (MDLs) were lower than 0.05μg/Kg for PCBs, 0.2μg/Kg for PAHs and PBDEs and 1ng/Kg for PCDD/Fs. The method is a faster and cheaper alternative to the time-consuming conventional method that has been used in most environmental laboratories.